Multi-channel EMG manifestations of upper-extremity muscle coordination imbalance among community-dwelling sarcopenic seniors - Haoru He; Xiaochu Wu; Na Li; Yi Jiang; Jiayuan He; Ning Jiang (BioMedical Engineering OnLine)
Abstract Background Sarcopenia is an age-related, insidious, crippling but curable degenerative disease if diagnosed and treated early. However, no accessible and accurate early screening method is available for community settings that does not require specialized personnel. One of the hallmarks of sarcopenia is the pathological changes of muscle fiber type composition and motor unit firing patterns. Surface electromyography (sEMG) may serve as an effective tool for detecting differences between healthy and sarcopenic individuals due to its superior wearability and accessibility compared to other screening methods such as medical imaging and bioimpedance measurements, making it ideal for community-based sarcopenic screening. Our study aims to explore sEMG biomarkers that can be used for screening or diagnosis of sarcopenia. Results We collected multi-channel sEMG signals from six forearm muscles of 98 healthy and 55 sarcopenic community-dwelling older adults. Participants performed grasp tasks at 20% and 50% of maximum voluntary contraction (MVC). Hexagons created by various EMG features, normalized with respect to respective MVC, and symmetry analyses were performed to estimate multi-muscle coordination patterns. An innovative index, namely incenter–circumcenter distance of muscle coordination (ICDMC), is proposed to discriminate between the healthy and sarcopenic groups. We utilized non-parametric tests to compare the ICDMC between the two groups, considering a p-value less than 0.05 statistically significant. The results showed that at 20% MVC, ICDMCs from root mean square (RMS), mean absolute value (MAV), slope sign changes (SSC) and wavelength (WL) showed statistically significant differences. More insights of this sEMG manifestation of sarcopenia were revealed by gender- and age-stratifications analyses. Conclusions Our results demonstrated that there are clear sEMG manifestations of altered muscle coordination in sarcopenic patients. More consistent force generation patterns were observed in the sarcopenic group, especially at lower contraction intensities. The novel ICDMC can quantify differences between sarcopenic and healthy muscle. These results warrant further research to further develop more accessible sarcopenia screening strategies in community settings based on electrophysiological measurements such as sEMG.